PENGARUH RETURN ON EQUITY, RETURN ON INVESTMENT, LOAN DEPOSIT RATIO, NET INTEREST MARGIN, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL, NET PROFIT MARGIN TERHADAP HARGA SAHAM - Munir Yapi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This research aimed to test the positive or negative influence, as well as whether the Return on Return On Equity,Return On Investment, Loan Deposit Ratio,Net Interest Margin, Operational Budgeting of Operational Income, Net Profit Margin towards investment value is significant or not, both simultanously and partially. Data used in this study were secondary data which are obtained from ICMD for go-public-banking-companies at BEI with sample from the year of 2010-2014. Sample taking used the method of purposive sampling and obtained as 25 samples that fulfilled the criterias. Technique of data analysis used the SPSS 21 method. Result showed simultanously that Return On Equity, Return On Investment, Loan Deposit Ratio, Net Interest Margin, Operational Budgeting of Operational Income, Net Profit Margin positively and significantly influenced the investment value. The result also showed partially that Return on Equity, Return on Investment positively and significantly influenced the investment value, Loan Deposit Ratio partially influenced negatively and was not significant towards investment value, Net Profit Margin influenced positively and was not significant towards investment value and Operational Budgeting of Operational Income, Net Profit Margin influenced negatively and significantly towards investment value.